The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/09291016.2019.1629088
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and fermentative profile of forage sorghum irrigated with saline water

Abstract: This study aimed to evaluate the nutritional and fermentative potential of silage of the forage sorghum Ponta Negra irrigated with saline water. The bromatological characteristics, losses and fermentative profile of sorghum silages were observed. For the bromatological characteristics of the sorghum plant, a decreasing linear behavior was observed for the contents of dry matter and organic matter while a positive linear effect was verified for crude protein and mineral matter as the leaching fractions were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…Sorghum (Sorghum bicolor (L.) Moench) is a tolerant/resistant crop to several abiotic constraints (Gois et al, 2019;Safdar et al, 2019;Shankar & Evelin, 2019;Castro & Santos, 2020). Its agricultural exploitation in semiarid regions is subject to several adverse environmental factors, potentially capable of causing negative effects on growth, development, production, and quality Simões et al, 2019;Guimarães et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum (Sorghum bicolor (L.) Moench) is a tolerant/resistant crop to several abiotic constraints (Gois et al, 2019;Safdar et al, 2019;Shankar & Evelin, 2019;Castro & Santos, 2020). Its agricultural exploitation in semiarid regions is subject to several adverse environmental factors, potentially capable of causing negative effects on growth, development, production, and quality Simões et al, 2019;Guimarães et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although the silage consisting only of cactus pear showed higher concentrations of N-NH 3 , the values found agree with Gois et al . (2019), who considered values of less than 10% of N-NH 3 /TN as indicative of adequate fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, high leaching fractions cause linear increases in the height, total leaf area, and water use efficiency in sorghum [8]. Gois et al [11], evaluating the leaching fractions of sorghum for silage production, reported a decrease in the dry matter content, mainly due to the accumulation of minerals in the plant; excess water resulted in increased moisture when the leaching fractions were higher.…”
Section: Introductionmentioning
confidence: 99%